2013 IEEE International Conference on Image Processing 2013
DOI: 10.1109/icip.2013.6738126
|View full text |Cite
|
Sign up to set email alerts
|

2-SiMDoM: A 2-Sieve model for detection of mitosis in multispectral breast cancer imagery

Abstract: In this paper, we propose a 2-Sieve model for the detection of mitosis in breast cancer multispectral images. Multiresolution wavelet features & Gray Level Entropy Matrix (GLEM) features have been computed for each candidate on all the spectral bands. A novel dimensionality selection algorithm has been introduced and its performance compared with other existing algorithms. Data imbalance and data cleaning have been taken care of using classical data mining techniques. Furthermore, a Second Sieve classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…They suggested that there should be a sufficient number of the training dataset. A. S. Tripathi et al,(2013) proposed a 2-Sieve model for mitosis detection. They have extracted Gray Level Entropy Matrix features and Multiresolution wavelet features on all the spectral bands.…”
Section: Review Based On Conventional Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that there should be a sufficient number of the training dataset. A. S. Tripathi et al,(2013) proposed a 2-Sieve model for mitosis detection. They have extracted Gray Level Entropy Matrix features and Multiresolution wavelet features on all the spectral bands.…”
Section: Review Based On Conventional Techniquesmentioning
confidence: 99%
“…Classical data mining technique and dimensionality selection technique had been used in this model. Their results show positive predictive value 73.04% and sensitivity 82.35% [29]. The approach presented in [30], uses the whole slide histological images for mitotic cell extraction and visualization, using the multi-resolution graph-based technique.…”
Section: Review Based On Conventional Techniquesmentioning
confidence: 99%
“…Wouwer et al also computed the DWT-based energy parameters for the automated identification of neoplastic nuclei in digitalized microscopic images and yielded good classification results in grading of invasive breast cancer. Tripathi et al investigated the ability of multi-level Daubechies wavelets, a commonly used form of DWT, to extract texture features for detecting mitosis in breast histopathological images, and showed a remarkable increase in the sensitivity measure over previous studies [27]. Lopez and Agaian combined wavelet and fractal features for Gleason grading of prostate cancer in histopathology images [28].…”
Section: Introductionmentioning
confidence: 99%